Determinants of Stock Return Movements with Independent Commissioners as Moderating Variables in Wholesale and Retail Trade Companieson the Indonesia Stock Exchange - Gavin Egianta Sembiring; Arthur Simanjuntak; Mitha Christina Ginting; Lamria Sagala (Jurnal Ilmiah Accusi, 2025)
This study aims to analyze the determinants of stock return movements with independent commissioners as moderating variables in wholesale and retail trade sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2022-2024. This study was conducted to analyze the determinants / factors that influence stock returns, including profitability, capital structure and company size with independent commissioners as moderating variables, namely profitability, capital structure, and company size on stock returns, as well as testing the role of independent commissioners. The approach used is quantitative with the moderated regression analysis (MRA) method using the SPSS 26 application. The research sample amounted to 26 companies. The results showed that partially Profitability has a positive and significant effect on Stock Returns, Capital structure has a negative and significant effect on Stock Returns, Company size has a positive and insignificant effect on Stock Returns. Profitability, Capital Structure, and Company Size simultaneously have a significant effect on the Stock Return variable. Independent commissioners are able to moderate the relationship between profitability and stock returns significantly. independent commissioners are able to moderate the relationship between capital structure and stock returns significantly. Independent commissioners are not able to moderate the relationship between company size and stock returns significantly